Bladder cancer in nonagenarians: a multicentre study of 123 patients. (26th July 2018) - Eredics, Klaus; Bretterbauer, Katharina M.; Comploj, Evi; Friedl, Alexander; Gschliesser, Tanja; Lenart, Sebastian; Seklehner, Stephan; Wimpissinger, Florian; Madersbacher, Stephan
Abstract : Objective: To investigate the oncological outcome of nonagenarians with bladder cancer, as a substantial rise in bladder cancer in the old‐old age group in the upcoming decades is expected, due to demographic changes and the peak incidence around the age of 85 years. The paucity of data of nonagenarians prompted us to investigate the outcomes of such patients. Patients and Methods: A retrospective, multicentre study was designed to assess patient demographics, tumour patterns, treatment strategies and outcome in patients aged ≥90 years treated at participating centres. Patients entered either as de novo or as recurrent cancer. The study period ranged from 01.01.2006 to 31.12.2016. Results: A total of 123 patients with a mean (range) age of 91 (90–99) years were recruited. The American Society of Anesthesiologists Physical Status Classification (ASA‐score) distribution was as follows: II, 38%; III, 50%; IV, 12%; and the male to female ratio 2.4:1. The median (range) follow‐up was 8 (1–132) months. In all, 60% of patients had a de novo cancer diagnosis. Histological findings revealed: pTa 39% ( n = 48), pT1 28.5% ( n = 35), and ≥pT2 33% ( n = 40). Overall, 67.5% patients had no recurrence, 25.2% one and 7.5% two or more. pTa tumours ( n = 48) recurred in 20 patients (42%), pT1 tumours ( n = 35) in 12 (34%), and ≥pT2 tumours ( n = 40) in six (15%). The median overall survival (OS) was 30.0 months for patients with pTa tumours, 14.0 months for pT1 tumours, and 6.0 months for ≥pT2 tumours. The overall mortality rate of patients with pTa tumours was 40%, with pT1 tumours at 60%, and ≥pT2 tumours 75%. The ASA‐score also had a strong influence on median OS after stratification by ASA‐score (II, 30 months; III, 12 months; IV, 4 months). Conclusions: In nonagenarians with bladder tumours, pTa/pT1/≥pT2 stages are almost evenly distributed and two‐thirds of patients had no recurrence after transurethral resection of the bladder. The mean OS was 1.3 years, and 6 months for ≥pT2 tumours. Further case‐series of patients in this specific age‐group are required to identify the best management of this increasing proportion of patients with bladder tumours.